Characterization of nuclear RNAi defective mutants in C. elegans - Lachowiec, Jennifer (My University, 2008)
Proper gene expression is crucial for all cellular processes, and changes in normal gene expression has been implicated in a number of human diseases, including asthma, heart disease, and cancer (Guajardo 2005, Tan 2002, Peng 2005). One form of gene regulation is RNA interference (RNAi). Using forward genetics, we have identified three genes required for nuclear RNAi. These genes regulate gene expression by targeting premRNA in the nucleus. We have found that three of these proteins likely act downstream of previously characterized RNAi proteins known to regulate mRNA levels. Based on sequence identity, two of these proteins are conserved. Our results strongly suggest the three proteins act in the same pathway. Greater understanding of the basic mechanisms of RNAi will help maximize its use as a therapeutic to treat disease.
16 p.
Keywords: Pharmacology; Genetics